Vitamin D effects on osteoblastic differentiation of mesenchymal stem cells from dental tissues - Posa, Francesca; Di Benedetto, Adriana; Colaianni, Graziana; Cavalcanti-Adam, Elisabetta A.; Brunetti, Giacomina; Porro, Chiara; Trotta, Teresa; Grano, Maria; Mori, Giorgio (Stem cells international, 2016)
1α,25-Dihydroxyvitamin D3 (1,25(OH)2D3), the active metabolite of vitamin D (Vit D), increases intestinal absorption of calcium and phosphate, maintaining a correct balance of bone remodeling. Vit D has an anabolic effect on the skeletal system and is key in promoting osteoblastic differentiation of human Mesenchymal Stem Cells (hMSCs) from bone marrow. MSCs can be also isolated from the immature form of the tooth, the dental bud: Dental Bud Stem Cells (DBSCs) are adult stem cells that can effectively undergo osteoblastic differentiation. In this work we investigated the effect of Vit D on DBSCs differentiation into osteoblasts. Our data demonstrate that DBSCs, cultured in an opportune osteogenic medium, differentiate into osteoblast-like cells; Vit D treatment stimulates their osteoblastic features, increasing the expression of typical markers of osteoblastogenesis like RUNX2 and Collagen I (Coll I) and, in a more important way, determining a higher production of mineralized matrix nodules.
Gesehen am 03.11.2020